2020
DOI: 10.1002/ange.202001608
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Magic‐Size Cluster Precursor Compounds into Ultrasmall CdS Quantum Dots with Enhanced Particle Yield at Low Temperatures

Abstract: Colloidal small‐size CdS quantum dots (QDs) are produced usually with low particle yield, together with side products such as the particular precursor compounds (PCs) of magic‐size clusters (MSC). Here, we report our synthesis of small‐size CdS QDs without the coexistence of the PC and thus with enhanced particle yield. For a conventional reaction of cadmium oleate (Cd(OA)2) and sulfur (S) in 1‐octadecene (ODE), we show that after the formation of the PC in the pre‐nucleation stage, the addition of tri‐n‐octyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…They are isomerization to binary ME MSCs, [2][3][4][5][14][15][16]18,34,35 substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), 17,[34][35][36][37]53,54 addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), 55 and fragmentation to QDs. 2,56 For the reaction of M and E precursors to ME QDs, the E precursor dominates the selfassembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry. The present finding of the E-dominated, magic self-assembly principle, together with the recent discovery of these binary and ternary MSCs and the successful synthesis of small-size QDs with enhanced yield, demonstrates that we are able to push further "chemical self-assembly".…”
Section: ■ Conclusionmentioning
confidence: 99%
“…They are isomerization to binary ME MSCs, [2][3][4][5][14][15][16]18,34,35 substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), 17,[34][35][36][37]53,54 addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), 55 and fragmentation to QDs. 2,56 For the reaction of M and E precursors to ME QDs, the E precursor dominates the selfassembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry. The present finding of the E-dominated, magic self-assembly principle, together with the recent discovery of these binary and ternary MSCs and the successful synthesis of small-size QDs with enhanced yield, demonstrates that we are able to push further "chemical self-assembly".…”
Section: ■ Conclusionmentioning
confidence: 99%
“…22−29 It was shown that the fragmentation of CdS PCs leads to the nucleation and growth of small-size CdS QDs with enhanced particle yield. 14 The control of the reactivity of MSCs (or other cluster intermediates) is essential to the non-classical nucleation and growth of group III−V QDs. 12 Gary et al showed that the reaction of primary amines with In 37 P 20 (O 2 CR) 51 removed In(O 2 CR) 3 subunits in an amine-bound form from the InP MSC.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive alternative to the single-step nucleation and growth of QDs is to use kinetically persistent, small inorganic clusters (<2 nm) as intermediates for the non-classical, multistep pathways of nucleation of QDs. Magic-sized clusters (MSCs) such as In 37 P 20 (O 2 CR) 51 , for example, can be used as cluster intermediates, providing single-source precursors (SSPs) for the homogeneous growth of InP QDs via hot injection . In 37 P 20 is one of the few MSCs whose single-crystal structures were identified .…”
Section: Introductionmentioning
confidence: 99%
“…Aer hot-injection of the tellurium precursor at 60 C, the temperature of the reaction mixture was increased to 120 C in 6 minutes. The mild hotinjection temperature is necessary to stabilize the MSCs because we found that ZnTe MSCs were not produced if the injection temperature was higher than 60 C. Some reactions may have already taken place at 60 C, 30,31 producing precursor compounds and monomers that are indispensable for the formation of MSC-323 at 120 C. 30,31 The rst aliquot was taken from the turbid white solution when the reaction proceeded for 2 hours at 120 C. The corresponding absorption spectrum (red curve in Fig. 1) presents a sharp peak at 323 nm along with a shoulder at 297 nm, which matches well with the characteristic absorption peak locations of ZnTe MSC-323.…”
Section: Resultsmentioning
confidence: 98%